Le concept d’intégration et de coordination dans une pratique de gestion d’information: analyse des politiques de gestion d’information du gouvernement fédéral canadien - Bergeron, Pierrette; Nauche, Benedicte; Dufour, Christine (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
This paper presents the results of an analysis of information management policies of the Canadian government that examined (1) the presence (or absence) of the assumption of integration and coordination of information functions; (2) how the concepts of integration and differentiation are defined, and what are the predetermined roles of information professionals in the policy instruments. .